ANGER EMOTIONS IN THE QUR’AN FROM AN ISLAMIC COMMUNICATION PSYCHOLOGY PERSPECTIVE - Benny Munardi; Syukur Kholil; Achar Zain (Fakultas Ushuluddin dan Dakwah UIN Raden Mas Said Surakarta, 2023)
This study aims to explain human anger in the Qur'an from the perspective of Islamic communication psychology. This is because anger is a dangerous emotion. This type of research aims to find the essence of words and sentences in the language paradigm. The subject of this research is self-communication in the Qur'an. The theory used is the cognitive dissonance theory. This type of research is qualitative with a thematic interpretation approach. Data collection techniques are interviews, literature review, and documentation. Data analysis techniques include collecting, reducing, presenting, and drawing credible conclusions. The research shows that there are four anger emotions in Islamic psychology communication, people who vent their anger, people who hold back their anger, people who forgive others, and people who do good to people who do evil. Based on Islamic communication psychology's perspective, the four actualizations of angry emotions add to the types of anger. Furthermore, these four types of angry emotions form a hierarchy so that individuals can learn to reach the highest hierarchy.